DESCRIPTION OF TALKS AND INTERESTS OF VA CLASSROOMS INPRES ILIGETANG SD, SIKKA DISTRICT: DESKRIPSI BAKAT DAN MINAT SISWA KELAS VA SD INPRES ILIGETANG KABUPATEN SIKKA - Marianus Yufrinalis; Anastsia Ale (SOSIOEDUKASI, 2019)
This study aims to determine the talents and interests that exist in each grade VA student at SD Inpres Iligetang. This type of research is a qualitative descriptive study. This research was conducted at SD Inpres Iligetang with 23 subjects. Data collection techniques using documentation, observation and interviews. The research data were analyzed using the Data Analysis Component according to Miles and Huberman with data collection analysis, data presentation, data reduction and the last one was drawing conclusions. The results showed that out of 23 VA grade students of SD Inpres Iligetang, 14 had the talent for playing football, 6 of them had the talent for drawing, 1 talent for singing, 1 talent for counting and 1 talent for dancing. While the interests of the VA class students of SD Inpres Iligetang include 4 students having an interest in playing footballs, playing music 1 person, drawing 2 people, learning Science 3 people, Mathematics 2 people, PKN 2 people, SBDP 1 person, Bindo 1 person, IPS 3 people, studied Religion 3 people and interest in singing 1 person. Based on the results of the research above, it can be concluded that every student has talents and interests, although not maximized due to the limited infrastructure for teachers and support from parents, but with an understanding of the talents and interests of each VA grade student of SD Inpres Iligetang, it should be noted and developed. by teachers, parents and the social environment in order to be good knowledge in educating and fostering students both at school and at home.